Spastic Quadreparesis - An Unusual Presentation of Sub-acute Combined Degenaration of Spinal Cord - Islam, Mohammad Syedul; Alam, Afroja; Masud, Md Adnan Hasan; Azad, Md Abul Kalam; Rahim, Md Abdur (Journal of Medicine, 2013)
We report a case of a 45-year-old gentleman presenting with numbness of both legs and hands. He has anemia, spastic quadriplegia with exageraterd tendon jerks with lose of vibration and position sense. Investigations revealed combined deficiency anemia with low serum vitamin B12. His MRI of cervicel spine was normal. Endoscopically he had atrophic gastritis. Ultimately he was dignosed as a case of sub-acute combined degeneration of spinal cord due to pernicious anemia. Patient was treated with injection vitamin B12 and well responded. On his followup, he had significant clinical improvement. This is a reversible condition if early diagnosis can be made and vitamin B12 therapy promptly given. Delayed treatment can result in irreversible neurological impairment. DOI: http://dx.doi.org/10.3329/jom.v14i1.14585 J MEDICINE 2013; 14 : 85-87